2001
DOI: 10.1046/j.1471-4159.2001.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

6‐Hydroxykynurenic acid and kynurenic acid differently antagonise AMPA and NMDA receptors in hippocampal neurones

Abstract: 6-Hydroxykynurenic acid (6-HKA), a derivative of kynurenic acid (KYNA) extracted from Ginkgo biloba leaves, was tested for its putative glutamate receptor (GluR) antagonism in comparison to the scaffold substance. The patch-clamp method together with fast-application techniques were used to estimate inhibition by 6-HKA and KYNA of agonist binding at NMDA and a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (NMDARs and AMPARs) of CA1 pyramidal neurones. 6-Hydroxykynurenic acid proved to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…7) Some constituents of EGBL are reported to suppress the response mediated by NMDA glutamate receptor. 13,14) Furthermore, in present study, EGBL is shown to exert an inhibitory action on non-NMDA glutamate receptor. Some neurodegenerative diseases are resulted from cell death induced by glutamate excitotoxicity and oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…7) Some constituents of EGBL are reported to suppress the response mediated by NMDA glutamate receptor. 13,14) Furthermore, in present study, EGBL is shown to exert an inhibitory action on non-NMDA glutamate receptor. Some neurodegenerative diseases are resulted from cell death induced by glutamate excitotoxicity and oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…7,11,12) EGBL and its constituents inhibit the response mediated by activation of NMDA receptor. 13,14) However, there is limited information concerning the effect of EGBL on response induced by activation of non-NMDA glutamate receptor. Kainate, an agonist for non-NMDA glutamate receptor, increases [Ca 2ϩ ]i in neurons via activations of non-NMDA glutamate receptor and voltage-dependent Ca 2ϩ channel.…”
Section: )mentioning
confidence: 99%
“…Epigenetic effects of Ginkgo administration with respect to the AMPA receptor [8] may very well represent one of the mechanisms of its action. On the other side, 6-hydroxykynurenic acid, one of the possible active ingredients of Ginkgo, developed an antagonistic action on AMPA-mediated channel activity using a patch clamp design in the hippocampus in vitro [9]. So for Ginkgo extracts Ph.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal cells. Cells were acutely isolated as described (34,35). Briefly, Tg(hGFAP͞EGFP) mice (36) from postnatal days 25-30 were decapitated, and their brains were dissected and cut into 300-m-thick slices in frontal orientation by using a vibratome (HM 650V; Microm International, Walldorf, Germany).…”
Section: Methodsmentioning
confidence: 99%